Analisis Faktor - Faktor Yang Berhubungan Dengan Praktik Aborsi Di Kecamatan Pegandon Kabupaten Kendal - Istiarti, Tinuk; Pietojo, Harbandinah; Kunsianah, Kunsianah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2006)
Background : Women are faced unique reproductive health threats, one of which is the unsafe abortion. Abortion remains a controversial having been in existence since the history of mankind was written. At the Central Java PKBI (Indonesian Family Planning Association) clinic, There are average of 50 to 70 abortion cases every month. The objective of this research is to find out the factors that influence abortion practices among women in Pegandon sub-district, Kendal regency.Method : The recearch itself is of the explanatory type using crossseectional approach. The population of the research are 6,344 women of the reproductive age in Pegandon sub-district, Kendal District. 32 women have taken as samples. Simple random sampling is done to obtain the quantitative data. The recearch is conducted through questionaires. To obtain the qualitative data, interviews with 5 respondents are thoroughly carried out. For data validation, interviews with 5 village midwives – who provide services for the respondents – are also thoroughly conducted. The data is then analyzed using SPSS software for Windows, version 10.0 as well as univariate, and multivariate methods.Result : The results of the analysis show that there is no correlation between the age, the level of education, the occupation, the marital status, the term of the pregnancy, the knowledge and attitude on the one side, and the abortion practice on the other. (p > 0,05). A significant correlation between the number of children and the abortion practice isfound in this research (p < 0,05). A multivariate analysis with logistic regression shows that the number of children variable is the main variable influencing the abortion practice in Pegandon sub-district in Kendal regency, (p<0,04) Keywords : Women of reproductive age, Abortion, Public Health.